Pengaruh Obat Calcium Channel Blocker Terhadap Terjadinya Xerostomia Pada Lansia Di Desa Gurah Kabupaten Kediri - Pebrianty, Valentina; Prehananto, Herlambang; Kusumastuti, Endah; Soebado, Bagus Musbadiono; Septommy, Catur (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2023)
Background: Hypertension is where systolic blood pressure reaches ≥140 mmHg and diastolic blood pressure ≥90 mmHg in routine examinations. Antihypertensive drugs help patients reduce high blood pressure, but on other hand, these drugs can impact the oral cavity. Amlodipine is one of the calcium-channel blockers (CCB) antihypertensive drugs. Directly and indirectly, antihypertensive drugs can affect salivary flow, causing oral symptoms, including is xerostomia. Xerostomia is a symptom or sign felt by someone with a dry mouth. Objective: To determine the effect of using calcium channel blocker (CCB) drugs on the occurrence of xerostomia in the elderly in Gurah Village, Kediri. Method: This study used an Observational Analytic design, with a cross-sectional design. The data obtained were then analyzed and interpreted to test the hypothesis using the Independent T-test with a nominal and ratio variable data scale. Results: The significant value of the Independent T-test on salivary flow rate was 0.032. (<0.05) which means there is a significant effect Conclusion: There is an effect of using calcium channel blocker drugs on the occurrence of xerostomia in the elderly in Gurah Village, Kediri. Keywords: Hypertension, Calcium Channel Blocker, Xerostomia, Salivary Flow Rate